PENGELOLAAN ALAT PERAGA BENDA MANIPULATIF DALAM PEMBELAJARAN MATEMATIKA DI SD - Yuliarni Yuliarni Yuliarni (UNIVERSITAS BENGKULU, 2016)
The purpose of the study was to get a more complete picture of management manipulative objects props to mathematics learning towards the fractional concept. The study conducted using classroom action research. Based on the results of the research to gain an average value of the student formative in the first cycle with an average value of 55.6, the second cycle with an average value of 74.8. It can be concluded that the use of management manipulative objects props to mathematics learning can improve the students' understanding of the fractional concept.Keyword: managemet, objects props, manipulative